Asset Recovery in Transnational Money Laundering Crimes Through International Legal Cooperation, Financial Intelligence Systems, Beneficial Ownership Transparency, and Digital Asset Tracing Governance - Jamaludin Jamaludin (Asosiasi Dosen Muda Indonesia, 2026)
Transnational money laundering has become one of the most complex global financial crimes threatening economic stability, national sovereignty, public governance, and international security systems. Criminal organizations increasingly utilize sophisticated financial networks, shell corporations, offshore jurisdictions, digital assets, cryptocurrency systems, and cross-border financial transactions to conceal illicit proceeds originating from corruption, narcotics trafficking, cybercrime, terrorism financing, human trafficking, tax evasion, and organized crime. Consequently, asset recovery has emerged as one of the most strategic mechanisms within anti-money laundering governance because confiscating criminal proceeds weakens the financial infrastructure sustaining transnational criminal activities. However, transnational asset recovery remains highly challenging due to jurisdictional fragmentation, banking secrecy, legal disparities, institutional corruption, technological complexity, and weak international coordination. This study aims to analyze strategies for strengthening asset recovery in transnational money laundering crimes through international legal cooperation, financial intelligence systems, beneficial ownership transparency, and digital asset tracing governance. The study employs a systematic literature review method by critically examining peer-reviewed international and national journal articles published between 2015 and 2026. The analysis integrates thematic analysis, comparative analysis, and narrative synthesis to identify governance patterns, institutional challenges, strategic innovations, and legal implications regarding transnational asset recovery systems.